Typologies of postnatal support and breastfeeding at two months in the UK: Response to comments by Harpur & Haddon. (May 2020) - Emmott, Emily H.; Page, Abigail E.; Myers, Sarah
Abstract: We welcome the comments by Harpur and Haddon (2020) on our paper on the typologies of social support and its associations with breastfeeding at two months in a UK sample. We share their concerns around the under-acknowledged costs of breastfeeding, and the need for a truly family-centred approach to breastfeeding support. However, they are mistaken to assume we do not view breastfeeding problems as an important cost of breastfeeding: We explicitly comment on breastfeeding challenges within our paper, and such challenges are theoretically incorporated into the "costs of breastfeeding" following an evolutionary anthropological framework. They are also incorrect in their statement that we recommend breastfeeding promotion messages to wider family members. In fact, we outline in our manuscript that breastfeeding promotional messages can have negative consequences for mothers, and are unlikely to be supportive. What we do suggest is a family-centred approach that recognises that women interact with, and may be supported by, a wide range of individuals (including fathers and grandmothers); and the importance of taking a nuanced approach to support without assuming that all types of support necessarily leads to "more breastfeeding." We hope our response is useful in clarifying the key points of our paper.